2020
DOI: 10.21606/drs.2020.120
|View full text |Cite
|
Sign up to set email alerts
|

Educating for design character in higher education: Challenges in studio pedagogy

Abstract: Some particular challenges in studio pedagogy arise from teaching for design character versus focusing solely on skills, knowledge or the cognitive processes of our students. In this paper, three authors with extensive combined experience in studio learning, teaching, and scholarship address these challenges via reflection on our own experiences of research and teaching and in-depth discussion with each other. We adopt a co/autoethnographic approach (Coia & Taylor, 2009), identifying a range of challenges we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Although it is more familiar to put the curriculum definition in the first rank, the overarching concept of common features became the main motto of the studio throughout the semester. Similar pedagogical paths also exist in the current literature (Deamer 2000;Boling et al 2020), which showed ways to configure higher issues as a pedagogical aim and link them with the strict formulations of the course descriptions in the program catalogues.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Although it is more familiar to put the curriculum definition in the first rank, the overarching concept of common features became the main motto of the studio throughout the semester. Similar pedagogical paths also exist in the current literature (Deamer 2000;Boling et al 2020), which showed ways to configure higher issues as a pedagogical aim and link them with the strict formulations of the course descriptions in the program catalogues.…”
Section: Resultssupporting
confidence: 54%
“…Similar pedagogical paths also exist in the current literature (Deamer 2000; Boling et al . 2020), which showed ways to configure higher issues as a pedagogical aim and link them with the strict formulations of the course descriptions in the program catalogues.…”
Section: Resultsmentioning
confidence: 99%
“…• The design studio (Boling et al, 2016), with an embedded focus on project-based work and critique as a means of socialization and formative assessment. This pedagogy was operationalized as the design lab sequence, where students worked in a custom-built lab with a range of prototyping equipment and collaborative workspaces.…”
Section: Historical Framing Of the Programmentioning
confidence: 99%
“…Yet rather than teachers dismissing these emotions as immature, or attempting to avoid them by excluding stressors like teamwork from the first‐year curriculum, engaging students in critical conversation about the multifaceted nature of collaborative work, as discussed below, can foster a space for transparency and mutual empathy between academics and students. As Boling et al (2020, 1874) note, studio‐based learning can be a painful process for students and one that requires an empathetic approach:
Rather than distancing ourselves from our students’ pain, addressing them as whole persons while they learn requires recognizing their pain, acknowledging that we have set up the circumstances for creating it, and constantly assessing how much of it is productive versus that which we could and should work to eliminate. This requires almost constant examination of what we are doing, what we expect to accomplish, and what assumptions we are making about the studio .
…”
Section: Literature Reviewmentioning
confidence: 99%